Situation Report: Hungary, 16 October 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Kadar in Moscow: No Substantial Change in Soviet-Hungarian Relations / by Alfred Reisch Prime Minister Lazar Visits Japan / by Alfred Reisch Hungarian-Japanese Trade and Economic Cooperation / by Alfred Reisch Gabcikovo-Nagymaros Hydroelectric Plant Project Defended / by Edith Markos More State Subsidies for Agriculture / by Laszlo Rasko